Standardization of preanalytical factors for minimal residual disease analysis in chronic myelogenous leukemia - Müller, Martin Christian; Hördt, Tanja; Paschka, Peter; Merx, Kirsten; La Rosée, Paul; Hehlmann, Rüdiger; Hochhaus, Andreas (Acta haematologica, 2004)
Optimal sample quality is a prerequisite to generate valid data in the detection of minimal residual disease (MRD) in leukemias. Thus, the risk of obtaining ‘false’-negative results is increased when both quality and quantity of RNA are suboptimal. Factors which affect the sensitivity and consequently the validity of MRD results are reviewed. RNA degradation in unstabilized peripheral blood (PB) samples does not play a major role in samples being processed on the day of blood collection. However, the simulation of sample shipping at room temperature with a delay of sample processing of up to 3 days causes a dramatic loss of intact RNA. RNA degradation can be prevented by the use of a bedside RNA stabilization system. Additionally, the stabilizing procedure is capable of keeping real-time quantitative polymerase chain reaction (RQ-PCR) results comparable whether the sample is processed immediately or with a delay of up to 3 days. Consistent quantitative data cannot be obtained with unstabilized blood samples. Furthermore, the optimum volume of PB required for MRD diagnostics in patients with BCR-ABL-positive chronic myelogenous leukemia in complete cytogenetic remission is revisited. Ten milliliters of PB is sufficient for processing on the day of blood collection whereas the use of only 5 ml PB may result in false-negative results. Standardization of preanalytical and analytical factors is necessary to provide a comparability of RQ-PCR results from different laboratories within multicenter studies. The definition of ‘undetectable BCR-ABL’ in an individual patient should take these preanalytical parameters into consideration.
Gesehen am 13.05.2022